Inge, Selwyn, and Gore: 1920s Anglican Responses to Newman’s Development of Doctrine - Bish, Jonathan James Peter (New blackfriars, 2025)
William Inge, Edward Gordon Selwyn, and Charles Gore represent three Anglican responses to John Henry Newman’s Essay on the Development of Doctrine. Development sought to account for doctrinal changes in Christianity by characterising Christianity as a ‘real idea’, expressing an object in the mind that can only be shown in its fullness by encounters with different philosophies over time. This was part of a wider intellectual movement in the 19th century away from static ideas of doctrinal history and towards more dynamic and subjective treatments. Inge, Selwyn, and Gore all make use of Newman after the First World War. Inge argues Newman abstracts historical facts from their realities, and abandons the old concept of tradition, where the church is the custodian of revelation, in favour of a relativistic concept, new in each generation. Selwyn makes use of Newman’s idea to argue for the autonomy of religious experience as a source of human knowledge mediated through religious traditions. Gore argues Newman enables ‘mobility’ in communicating Christianity to different cultures but argues development can be used justify distortions of the first revelation. The test of their authenticity should be whether they are inclusive of those Christ would be inclusive.